Some Results on Fractional m-Point Boundary Value Problems. (6th August 2021) - Zhu, Huijuan; Han, Baozhi; Shen, Jun
Abstract : In this paper, we will apply some fixed-point theorems to discuss the existence of solutions for fractional m-point boundary value problems D 0 + q u ″ t = h t f u t, t ∈ 0, 1, 1 < q ≤ 2, u ′ 0 = u ″ 0 = u 1 = 0, u ″ 1 − ∑ i = 1 m − 2 α i u ‴ ξ i = 0 . In addition, we also present Lyapunov's inequality and Ulam-Hyers stability results for the given m-point boundary value problems.